Stage-Specific Survival in Breast Cancer in Chinese and White Women: Comparative Data Analysis - Jun Wang; Juan Zhou; Lei Liu; San-Gang Wu (JMIR Publications, 2022)
BackgroundStage-specific survival, according to the eighth edition of the American Joint Committee on Cancer (AJCC) pathological prognostic staging (PPS) on breast cancer (BC), between Chinese and White American women remains unclear. ObjectiveThis study aimed to assess stage-specific survival in BC between Chinese and White American women according to the eighth AJCC PPS. MethodsWe included Chinese and White American women with BC diagnosed between 2010 and 2018 from the Surveillance, Epidemiology, and End Results database. A chi-square test, the Kaplan-Meier method, a receiver operating characteristic (ROC) curve, and multivariate Cox proportional hazards models were used for data analysis. ResultsWe included 376,818 individuals in this study: 369,522 White American and 7296 Chinese. Of them, 149,452 (39.7%) migrated from the seventh AJCC anatomic staging (AS) to the eighth AJCC PPS, 22,516 (6.0%) were upstaged, and 126,936 (33.7%) were downstaged. With a median follow-up duration of 44 months, the 5-year overall survival and cancer-specific survival (CSS) for the entire group were 87.4% and 95.9%, respectively. The seventh AJCC AS (P<.001) and the eighth AJCC PPS (P<.001) could significantly predict the survival outcomes of BC, and multivariate analysis revealed that both staging systems were significant prognostic indicators of CSS. The ROC curve revealed that the PPS had a better discriminating ability than the AS (area under the curve [AUC] 0.769 vs 0.753, P<.001). Similar trends were observed after stratification by the 2 ethnic groups. The eighth AJCC PPS had better discriminating ability than the seventh AJCC AS among both White American (AUC 0.769 vs 0.753, P<.001) and Chinese patients (AUC 0.790 vs 0.776, P<.001). In the seventh AJCC AS, Chinese women had better CSS in stage IA (P=.02), stage IIA (P=.005), and stage IIIB (P=.04) disease than White American women, but no significant CSS was observed in stage IB, IIB, IIIA, and IIIC disease between the 2 ethnic groups. Regarding the eighth AJCC PPS, Chinese women had better CSS in stage IA (P=.002) and IIIA (P=.046) disease than White American women, and CSS was similar in Chinese and White American women in other substages. ConclusionsThe eighth AJCC PPS has a similar discriminative ability between White American and Chinese individuals with BC compared with the seventh AJCC AS. Therefore, the eighth AJCC PPS is also applicable to Chinese individuals with BC.